EDUPRENEURSHIP 5.0: KULINER TASIKMALAYA UNTUK GENERASI DIGITAL - Eva Alawiah; Risbon Sianturi; Irma Siti Anisa; Nizza Nadya Rachmani; Elsakira, Lena (CV. Denasya Smart Publisher, 2024)
This study discusses the concept of